1997
DOI: 10.1007/bf00941800
|View full text |Cite
|
Sign up to set email alerts
|

Soybean agglutinin binding as a useful prognostic indicator in stomach cancer

Abstract: Soybean agglutinin (SBA)-binding carbohydrate expression was studied immunohistochemically in 353 primary gastric carcinomas. The overall rate of positive SBA staining was 23% (81/353), and positive SBA staining was significantly correlated with tumor size, macroscopic tumor type, depth of invasion, lymph node metastasis, and venous invasion (P < 0.05). Moreover, patients with tumors that were immunoreactive for SBA demonstrated significantly higher survival (P < 0.01). From these findings we conclude that car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…37 They are also involved in a variety of biomedical applications, 37,38 including fractionation of bone marrow cells, 39 the treatment of ulcerative colitis, 40 and other biologic uses, 41,42 such as cancer diagnosis and treatment. Lectins have been used as diagnostic reagents for stomach cancer, 43 in cancer treatment combined with anticancer drugs, 44 and in the removal of tumor cells from bone marrow, 45,46 as well as in targeted drug delivery treatments. 47…”
Section: Lectins: Structure Binding Speci Cities and Physiologic Efmentioning
confidence: 99%
See 1 more Smart Citation
“…37 They are also involved in a variety of biomedical applications, 37,38 including fractionation of bone marrow cells, 39 the treatment of ulcerative colitis, 40 and other biologic uses, 41,42 such as cancer diagnosis and treatment. Lectins have been used as diagnostic reagents for stomach cancer, 43 in cancer treatment combined with anticancer drugs, 44 and in the removal of tumor cells from bone marrow, 45,46 as well as in targeted drug delivery treatments. 47…”
Section: Lectins: Structure Binding Speci Cities and Physiologic Efmentioning
confidence: 99%
“…59,60 Numerous experimental and clinical studies have been conducted to investigate the biologic behavior of malignant cells, and have shown that soybean lectin is a useful prognostic indicator in stomach cancer. 43 Cellular interactions appear to play an important role in the metastatic process and the clinical behavior of tumors and may be mediated partially by cellsurface proteins that are closely associated with the transformation of cells. Lectins that bind speci cally to certain polysaccharides can be conjugated to histochemical markers, making it possible to study the patterns of glycoconjugate expression by cells and tissues, as well as the alterations, which may occur during malignant transformation.…”
Section: Lectins: Structure Binding Speci Cities and Physiologic Efmentioning
confidence: 99%
“…Benbassat et al (1987) reported the use of fluorescein-isothiocyanate-conjugated SBA to assess the stage of lymphoid cell differentiation in human leukemic-lymphoma cell lines and showed that a gradual increase in SBA labelling was correlated with stages of the cell differentiation as reflected by increased fluorescence intensity. High affinity binding of fluorescent SBA conjugates to other types of cancer cells has also been shown, including mouse lymphoma T cells (Reese and Chow 1992) and human gastric carcinoma cells (Terashima et al 1997). Fluorescent SBA conjugates are also reported to selectively bind to murine glial cells (Luth et al 1992) and the zona pellucida of the mammalian egg (Aviles et al 1997).…”
Section: Discussionmentioning
confidence: 92%
“…5 Recent studies using monoclonal antibodies (mAbs) have demonstrated an intimate relationship between the aggressive growth of gastric cancer and expression of carbohydrate epitopes, such as sialyl Tn (STn) and sialyl-Lewis a (SLe a ) antigens. [6][7][8][9][10][11][12][13] On the other hand, there is little information about lectin-binding carbohydrates, [14][15][16] even though dynamic changes in carbohydrate expression on epithelial cells of the gastric wall have been demonstrated by lectin histochemistry. [17][18][19][20][21] Furthermore, none of the studies using mAbs have focused on early gastric cancer.…”
Section: Introductionmentioning
confidence: 99%